STRATEGI PENGEMBANGAN DESA WISATA BRAYUT MENJADI WISATA UNGGUL BERBASIS EKOWISATA - , SITI RUKIAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Old times in tourism development using the concept of mass tourism. is tourism that prioritize economic development as much as possible and pay less attention to the condition of the natural surroundings . Now, as time began to feel the negative effects of mass tourism is the environmental damage . therefore new ideas emerged in the development of tourism, called the development of sustainable tourism is tourism development that emphasizes environmental sustainability or also called ecotourism . Application of these concepts one of which is in the Village, which is the current tourist trend . Object of research by the author is Village Tourism Brayut , Pandowoharjo , Sleman , Yogyakarta , who pioneered since 1999 and is the oldest village in Sleman Tourism . Data collection techniques that authors use the method of interview , observation and study the literature . Of interview , observation and study the literature , the writers describe the implementation of ecotourism in Brayut Tourism Village , and the authors found that development constraints occur there in . From the data processing is known ecotourism activities contained in the Brayut Tourism Village is tracking , camping , and botanical study with a land area of ecotourism by 40 % , the rest is residential.tourist who came to the Brayut Tourism Village is ecotourism from various regions , including Java , outside Java , and abroad . From 2007 to May 2013 as many as 11 912 tourists as 50 % are students ( ages 6-17 years ) , students from various faculties 9 % , and the public as much as 41 % . Of travelers and 11 912 , 2 % are foreign tourists and 98 % were domestic tourists with total as many as 275 as many as 11,637 domestic tourists and travelers . This shows the level of traffic is still dominated by domestic tourists. Further development of resistance , the authors describe the direction for future tourism development such as the development of alternative tracking trails physical form and the concept of outdoor tours , attractions such as the development of the environment and conservation of rare plant conservation , environmental awareness , and the development of additional amenities such as trash cans in the area of Village Tourism , the addition of markers (signing ) to ban or warning as ban throwing garbage in the river